Perception of Rural Farmers on Impact of Economic Tree Crops on Environmental Sustainability in Delta State, Nigeria - Emuh, Fidelis Nduka; Achoja, Felix Odemero; Obodaya, Oghenesarome (Discoveries in Agriculture and Food Sciences, 2023)
The Government of Nigeria has engaged in the campaign for tree planting at both community and national scale due to its environmental benefits and mitigation of climate change hazards. The perception of indigenous people on the environmental benefits could influence their actions. It is important to broaden clarify the existing body of knowledge on the perception of indigenous people on the environmental benefits of economic tree crops. This study empirically investigated the perception of rural farmers with respect to the impact of economic tree crops on environmental sustainability. Cross sectional data were collected with structure questionnaire from randomly drawn sample of 150 farmers. Primary data collected were analyzed using relevant descriptive and inferential statistical tools (mean, percentage, standard deviation, logistic regression and chi-square).The test of hypothesis indicated no significant difference in the perception of respondents with respect to the impact of economic tree crops on environmental sustainability (i.e. farming households expressed uniform opinion on the environmental impact of economic trees. It was recommended that international organizations such as World Bank, United Nations etc with poverty alleviation and climate mitigating policies targeted at developing countries should key into the dualistic potentials of economic trees in order to achieve their goals.